2015
DOI: 10.14257/ijhit.2015.8.6.09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molar Ratios on Compressive Strength of Modified Magnesium Oxysulfate Cement

Abstract: To determine the effect of molar ratios on compressive strength of magnesium oxysulfate cement (MOS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
(9 reference statements)
2
3
0
Order By: Relevance
“…Further increase of H gives accumulation of MH and gradually results in the collapse of paste structure, demonstrating the low water-resistance of MOS cement paste. Similar experimental results have been reported in [56], in which XRD results exhibits stronger peak intensity of Phase 517 and weaker peak intensity of MH when H = 20 than H = 28, indicating the decomposition of Phase 517 and generation of more MH. It is suggested that when H is around 14-16, the only equilibrium phase is Phase 517, which is favorable to the strength development for MOS cement paste.…”
Section: Influence Of Molar Ratios On Hydrated Productssupporting
confidence: 88%
See 1 more Smart Citation
“…Further increase of H gives accumulation of MH and gradually results in the collapse of paste structure, demonstrating the low water-resistance of MOS cement paste. Similar experimental results have been reported in [56], in which XRD results exhibits stronger peak intensity of Phase 517 and weaker peak intensity of MH when H = 20 than H = 28, indicating the decomposition of Phase 517 and generation of more MH. It is suggested that when H is around 14-16, the only equilibrium phase is Phase 517, which is favorable to the strength development for MOS cement paste.…”
Section: Influence Of Molar Ratios On Hydrated Productssupporting
confidence: 88%
“…Further increase of H gives accumulation of MH and gradually results in the collapse of paste structure, demonstrating the low water-resistance of MOS cement paste. Similar experimental results have been reported in [56], in which XRD results exhibits stronger peak intensity of Phase 517 and weaker peak intensity It can be observed that large M makes for the formation of Phase 517 and MH in Figure 4. When M is equal to 3, Phase 517 begins to appear in the MOS paste.…”
Section: Influence Of Molar Ratios On Hydrated Productssupporting
confidence: 87%
“…According to previous studies, the mechanical properties of cement depend on the phase composition, the microscopic appearance of the hydration products of the cement slurry and the raw material ratio. According to Li's report [24], the selection of the M was limited by the rheology (upper limit) and processability (lower limit) of the mixture. This section primarily studies the effects of the M on the performance of the MOCFC.…”
Section: Molar Ratio (M)mentioning
confidence: 99%
“…However, only the acid solubility and plugging ability of the MOC cement were studied. Magnesium oxysulfate (MOS) cement has low hygroscopicity, making it easier to transport and giving it a longer shelf life. , Commonly, the strength of the MOS cement is lower due to the limited solubility of MgSO 4 ·7H 2 O at ambient temperature. However, this can be effectively improved by raising temperatures or by adding modifying additives. , Cui et al studied the fundamental properties and plugging performance of the MOS cement.…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium oxysulfate (MOS) cement has low hygroscopicity, making it easier to transport and giving it a longer shelf life. 25 , 26 Commonly, the strength of the MOS cement is lower due to the limited solubility of MgSO 4 ·7H 2 O at ambient temperature. However, this can be effectively improved by raising temperatures or by adding modifying additives.…”
Section: Introductionmentioning
confidence: 99%